Prevalence of posttraumatic stress disorder among road traffic accident survivors: A PRISMA-compliant meta-analysis. Issue 3 (January 2018) - Lin, Wanli; Gong, Lina; Xia, Miaojuan; Dai, Wenjie
Abstract: Background: Involvement in road traffic accidents (RTAs) may put individuals at increased risk for a wide range of psychiatric disorders, among which posttraumatic stress disorder (PTSD) presents a public health issue. However, a great disparity was observed among studies exploring the prevalence of PTSD among RTA survivors. This meta-analysis aimed to explore the pooled prevalence of PTSD among RTA survivors. Methods: Electronic databases of PubMed, Embase, Web of Science, PsycARTICLES, PsycINFO, and CINAHL were searched to identify relevant studies. Study selection and data extraction were conducted independently by 2 investigators, and a meta-analysis was performed to synthesize the data. Heterogeneity among studies was evaluated using the Cochran Q test and quantified using the I 2 statistic. Subgroup analyses were performed to identify the source of the heterogeneity. The possibility of publication bias was assessed using Egger linear test. Results: Fifteen eligible studies containing 6804 RTA survivors were identified in this meta-analysis, of which 1489 were identified with PTSD. The pooled prevalence of PTSD among RTA survivors was 22.25% (95% confidence interval: 16.71%–28.33%). A high degree of heterogeneity was observed across studies ( I 2 = 97.1%, P < .001), with reported PTSD prevalence ranging from 6.3% to 58.3%. Subgroup analyses found that the prevalence of PTSD among RTA survivors varied significantly across studies in relation to the instrument used to assess PTSD, country, race, gender, and education level ( P < .05). Conclusion: The high pooled prevalence of PTSD among RTA survivors found in this study significantly underscores the need for providing timely and effective intervention strategies for RTA survivors.